Perancangan Model Simulasi Sistem Pencatatan Data Otomatis Menggunakan RFID pada Proses Assembling (Studi Kasus: Laboratorium Teknik Industri UMS) - Ningroem, Novie Tyas Noegroho, Ratnanto Fitriadi, S.T., M.T, Ahmad Kholid Al Ghofari, S.T., M.T (2015)
Data recording system in the assembling area which still done manually in many cases, is deemed to be ineffective because it will take a longer time to process the data. Moreover, the process of recording data manually tends to have a higher potential of error, because the process relies heavily on the accuracy of the operators who perform the data recording. Therefore, it is necessary to process the data recording automatically. The purpose of the implementation of this research is to design a model of a simplification of the real system in the manufacturing industry into a laboratory-scale system Department of Industrial Engineering University of Muhammadiyah Surakarta, identifying the system requirements for the application of automated data recording system (automatic data capture) using RFID, as well as designing activities simulation data recording automatically (automatic data capture) using RFID, which is carried out at the Laboratory of Industrial Engineering Department of the University of Muhammadiyah Surakarta. Research on automatic data recording system is implemented by modeling the system. Modeling process begins by conceptualizing the model, namely the inductive approach, by observing a number of symptoms individually, and then formulates it in draft form. Similarly, with this study, in which symptoms occur in assembling activities in a manufacturing industry becomes a reference of the model to be created. After successfully model the state of the real system, then the stages of verification and validation of the model. Results of this study were successfully modeled 4 types of automated data recording system. Such as determining the type of major components, determining the type of supporting components, determining the number of components in the store, as well as error detecting while input the component. Fourth system is then designed into a program using RFID automatic data recording. Keywords: